TALENT ANALYTICS AND TALENT MANAGEMENT: - A SYSTEMATIC LITERATURE REVIEW IN IMPROVING ORGANISATIONAL PERFORMANCE. - Mahato, Deepti Kumari; Prasad, Lalit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Talent analytics has emerged as a new trend and challenge in the business context emphasizing the strategic value of Human Resource Management (HRM) to the top management leaders. The Talent Analytics System is built to calculate and predict the retention of the candidate before they are hired. The organisation will be able to make the hiring decision whether to hire or not to hire the candidate by looking at their predicted retention result. A comprehensive literature review analysis was done to understand how talent analytics and talent management plays an important role in improving organization performance. This study is conceptual in nature as it discusses some aspects like definitions, importance, process, models, challenges etc. under Talent analytics.